Glycosylation Pattern and in vitro Bioactivity of Reference Follitropin alfa and Biosimilars - Riccetti, Laura; Sperduti, Samantha; Lazzaretti, Clara; Klett, Danièle; De Pascali, Francesco; Paradiso, Elia; Limoncella, Silvia; Potì, Francesco; Tagliavini, Simonetta; Trenti, Tommaso; Galano, Eugenio; Palmese, Angelo; et al. (Frontiers in Endocrinology, 2019)
Recombinant follicle-stimulating hormone (FSH) (follitropin alfa) and biosimilar preparations are available for clinical use. They have specific FSH activity and a unique glycosylation profile dependent on source cells. The aim of the study is to compare the originator (reference) follitropin alfa (Gonal-f®)- with biosimilar preparations (Bemfola® and Ovaleap®)-induced cellular responses in vitro. Gonadotropin N-glycosylation profiles were analyzed by ELISA lectin assay, revealing preparation specific-patterns of glycan species (Kruskal-Wallis test; p < 0.05, n = 6) and by glycotope mapping. Increasing concentrations of Gonal-f® or biosimilar (1 × 10−3-1 × 103 ng/ml) were used for treating human primary granulosa lutein cells (hGLC) and FSH receptor (FSHR)-transfected HEK293 cells in vitro. Intracellular cAMP production, Ca2+ increase and β-arrestin 2 recruitment were evaluated by BRET, CREB, and ERK1/2 phosphorylation by Western blotting. 12-h gene expression, and 8- and 24-h progesterone and estradiol synthesis were measured by real-time PCR and immunoassay, respectively. We found preparation-specific glycosylation patterns by lectin assay (Kruskal-Wallis test; p < 0.001; n = 6), and similar cAMP production and β-arrestin 2 recruitment in FSHR-transfected HEK293 cells (cAMP EC50 range = 12 ± 0.9–24 ± 1.7 ng/ml; β-arrestin 2 EC50 range = 140 ± 14.1–313 ± 18.7 ng/ml; Kruskal-Wallis test; p ≥ 0.05; n = 4). Kinetics analysis revealed that intracellular Ca2+ increased upon cell treatment by 4 μg/ml Gonal-f®, while equal concentrations of biosimilars failed to induced a response (Kruskal-Wallis test; p < 0.05; n = 3). All preparations induced both 8 and 24 h-progesterone and estradiol synthesis in hGLC, while no different EC50s were demonstrated (Kruskal-Wallis test; p > 0.05; n = 5). Apart from preparation-specific intracellular Ca2+ increases achieved at supra-physiological hormone doses, all compounds induced similar intracellular responses and steroidogenesis, reflecting similar bioactivity, and overall structural homogeneity.